Local differentiation in tree growth responses to climate. Issue 8 (21st August 2018) - Canham, Charles D.; Murphy, Lora; Riemann, Rachel; McCullough, Richard; Burrill, Elizabeth
Abstract: Many temperate tree species have extraordinarily broad distributions along gradients of temperature and precipitation. But it is not clear in most species whether this reflects very broad tolerance of climate conditions, or a high degree of genetic differentiation or phenotypic acclimation in their responses to local climate. Provenance trials and common garden experiments indicate that at least some tree species of the temperate forests of eastern North America show genetic differentiation in growth as a function of climate, although these studies have been largely limited to measurements on growth of seedlings and saplings. To test for evidence of either adaptation or acclimation in adult response to local climatic conditions, we used data from over 23, 000 tree cores collected by the U.S. Forest Inventory and Analysis program in the 1980s for 14 tree species distributed in states from Maine to Ohio. We tested a suite of alternate models for interannual variation in radial growth as a function of (1) tree age, (2) size, (3) temperature, and (4) precipitation. The models included climate variables from both the current and previous year. The alternate models allowed us to test whether growth was best predicted from absolute values of the climate variables, or from deviation of current or previous year climate from long‐term average at the location of an individual tree core. In all 14 species, models that used deviation from local, long‐term mean climate were superior, indicating that all 14 species showed strong adaptation or acclimation to local climate. In most of the species, growth was highest in years that were cooler and wetter than long‐term average at a location. The analysis does not allow us to distinguish between genetic differentiation and phenotypic acclimation responses. If the results are genetically based, trees within a given location could be much more sensitive to climate change than indicated by the very broad geographic distributions of these temperate tree species, but if the results are phenotypic, this would represent local acclimation that could help buffer species in the face of climate change.